STUDY OF FRICTION STIR WELDING TOOL’S COATING MATERIAL (TiAlN) FOR TUNGSTEN CARBIDE COBALT - Kamaruddin, Haikal (IRC, 2020)
This project aims to compare and see the performance of the material of tungsten carbide cobalt (WC-Co) with a different coating (6%, 9% and 12%) with and without the coating (titanium aluminium nitrate (AlTiN) for friction stir welding (FSW). The proposed material uses two kinds of an experiment which is Vickers hardness test and scratch test data to compare and see the material performance. The higher the cobalt content, the higher the hardness of the materials. In the other hand, the adhesion of coating will decrease as the higher the cobalt content in the materials. The reason why the performance of the material needs to be compared because each of the material carries a different value of hardness and adhesion strength.